Meltwater flow through a rapidly deglaciating glacier and foreland catchment system: Virkisjökull, SE Iceland - Verity Flett; Louise Maurice; Andrew Finlayson; Andrew R. Black; Alan M. MacDonald; Jez Everest; Martin P. Kirkbride (Hydrology Research, 2017)
Virkisjökull is a rapidly retreating glacier in south-east Iceland. A proglacial lake has formed in the last ten years underlain by buried ice. In this study we estimate water velocities through the glacier, proglacial foreland and proglacial river using tracer tests and continuous meltwater flow measurements. Tracer testing from a glacial moulin to the glacier outlet in September 2013 demonstrated a rapid velocity of 0.58 m s−1. This was comparable to the velocity within the proglacial river, also estimated from tracer testing. A subsequent tracer test from the same glacial moulin under low flow conditions in May 2014 demonstrated a slower velocity of 0.07 m s−1. The glacier outlet river sinks back into the buried ice, and a tracer test from this sink point through the proglacial foreland to the meltwater river beyond the lake indicated a velocity of 0.03 m s−1, suggesting that an ice conduit system within the buried ice is transferring water rapidly beneath the lake. Ground penetrating radar profiles confirm the presence of this buried conduit system. This study provides an example of rapid deglaciation being associated with extensive conduit systems that enable rapid meltwater transfer from glaciers through the proglacial area to meltwater rivers.